(untitled) (Architecture Image Studies, 2025)
Introduction: Notary honorarium reflects not only the value of professionalism but also contributes to creating justice in legal services. This honorarium regulation is governed by rules aimed at ensuring transparency and preventing unfair competition among notaries. This research aims to examine the urgency and mechanism of reconstructing notary honorarium regulations, which prioritize minimum and maximum standards based on service complexity. Methodology: The research method used is doctrinal research with a normative juridical approach. The study results indicate that the current regulation of notary honorarium is stipulated in Article 36 of the Notary Position Law, which determines the amount of honorarium based on the economic and sociological value of the deed made. The effectiveness of the honorarium regulation is still inadequate, evidenced by weak supervision and the application of sanctions that do not provide a deterrent effect. The reconstruction of more specific notary honorarium regulations, with the establishment of clear minimum and maximum standards, transparent procedures, and a more effective supervision and sanction model, is crucial to prevent unfair competition among notaries. The research purpose is to give an analysis on the effectiveness of honorarium regulation in the notary service operations. The scientific contribution from this research is that it provides the latest information on the effectiveness of honorarium regulation in the notary service operations.